JOB STRESS OF TEACHERS WORKING IN THE HIGH SCHOOLS IN THOOTHUKUDI DISTRICT - Dr. R. Thangadurai (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper focuses its attention on the job stress of teachers working in the high schools in Thoothukudi district of Tamilnadu State. The researcher used survey method research. The population of the study is all the teachers working in the high schools in Thoothukudi district. From the population, the researcher has chosen 200 teachers using simple random sampling technique. The data were collected using a self-constructed scale for measuring the job stress of teachers. Mean, SD and ‘t’ test were used for analysing the data. The findings of the study revealed that majority of the high school teachers have reported high level job stress and the locality of school has played a significant role in influencing the job stress of teachers